PERJANJIAN ASURANSI MELALUI TELEMARKETING DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 - Didik Wahyu Sugiyanto (MIMBAR YUSTITIA, 2017)
Development in the field of insurance sparked a new idea related to the form of marketing in offering its services products. some insurance companies in offering their services is to use the telephone communication network called Telemarketing. the product of this insurance service uses a form of pemasaraan where the prospective insured party can buy insurance products without the need to meet face to face and signed a written agreement. In Article 255 of the Criminal Code states that the insurance must be made in writing in the form of a deed called Polis. Records of Telephone Disclosures in insurance agreements through Telemarketing as evidence in the dispute of civil cases are indeed valid to be made or submitted as evidence evidenced by Article 5 of the ITE Law. The recording of telephone conversations in the category of evidence in accordance with Article 1866 of the Civil Code is included in the form of evidence of "Conspiracy" so that this affects from the legal force of this evidence which is not the same as the legal force such as the perfect written proof so that other evidence must be presented such as letters or written evidence.